The amber spyglass - Pullman, Philip, 1946- (New York : Alfred A. Knopf, 2000)
Lyra and Will find themselves at the center of a battle between the forces of the Authority and those gathered by Lyra's father, Lord Asriel.
Sequel to: The subtle knife.
950
Accelerated Reader AR
Keywords: Fantasy